2010
DOI: 10.4088/jcp.09m05604blu
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Anger Management Therapy in a Rural Population of Combat Veterans With Posttraumatic Stress Disorder

Abstract: Clinical and process outcomes indicate delivering cognitive-behavioral group treatment for PTSD-related anger problems via videoteleconferencing is an effective and feasible way to increase access to evidence-based care for veterans residing in rural or remote locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
215
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(246 citation statements)
references
References 25 publications
10
215
1
1
Order By: Relevance
“…Chiang et al 13 reported that family caregivers of heart failure patients who received telenursing consultations experienced significant reductions in caregiver burden and stress and significant improvements in family function. Morland et al, 14 in a study of veterans who had posttraumatic stress disorder, found that the use of videoconferencing resulted in reductions in anger symptoms. Moreover, many authors have reported that patients enrolled in telemedicineenabled ICU programs experience improved clinical outcomes, reductions in complications, and improved evidence-based bundle compliance compared with those not enrolled in programs.…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al 13 reported that family caregivers of heart failure patients who received telenursing consultations experienced significant reductions in caregiver burden and stress and significant improvements in family function. Morland et al, 14 in a study of veterans who had posttraumatic stress disorder, found that the use of videoconferencing resulted in reductions in anger symptoms. Moreover, many authors have reported that patients enrolled in telemedicineenabled ICU programs experience improved clinical outcomes, reductions in complications, and improved evidence-based bundle compliance compared with those not enrolled in programs.…”
Section: Discussionmentioning
confidence: 99%
“…Four reports only briefly stated in the results section [29], methods section [30,31] or the discussion [32] that no adverse events occurred or were observed, without providing information about how these adverse events were defined or monitored.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…As expected, antisocial personality traits were associated with smaller decreases in trait anger, anger expression, and physical aggression during treatment. In a study examining the effectiveness of a telemedicine modality, Morland et al implemented a cognitive-behavioral group anger management treatment for Veterans with PTSD in which treatment was delivered with the therapist present or via video teleconferencing [68]. Both treatment groups demonstrated similar reductions in anger symptoms.…”
Section: Effective Interventions For Anger and Aggressionmentioning
confidence: 99%